Cinnamaldehyde Ameliorates Dextran Sulfate Sodium‐Induced Colitis in Mice by Modulating TLR4/NF‐κB Signaling Pathway and NLRP3 Inflammasome Activation. Issue 2 (27th January 2023) - Tan, Xiaofen; Wen, Yifan; Han, Zhijun; Su, Xuyang; Peng, Jing; Chen, Feng; Wang, Yadong; Wang, Tianming; Wang, Changzhong; Ma, Kelong
Abstract: Ulcerative colitis (UC) is a chronic inflammatory gastrointestinal disease mainly associated with immune dysfunction and microbiota disturbance. Cinnamaldehyde (CIN) is an active ingredient of Cinnamomum cassia with immunomodulatory and anti‐inflammatory properties. However, the therapeutic effect and detailed mechanism of CIN on UC remains unclear, and warrant further dissection. In this study, network pharmacology and molecular docking analyses were introduced to predict the potential targets and mechanism of CIN against UC. The therapeutic effect and the predicted targets of CIN on UC were further validated by in vivo and in vitro experiments. Seven intersection targets shared by CIN and UC were obtained, and four hub targets, i. e., toll‐like receptor 4 (TLR4), transcription factor p65 (NF‐κB), NF‐kappa‐B inhibitor alpha (IκBα), prostaglandin G/H synthase 2 (COX2) were acquired, which were mainly involved in NF‐κB, tumor necrosis factor (TNF), Toll‐like receptor and NOD‐like receptor signaling pathways. CIN alleviated the symptoms of dextran sulfate sodium (DSS)‐induced colitis by decreasing the disease active index (DAI), restoring colon length, and relieving colonic pathology. CIN attenuated systemic inflammation by reducing serum myeloperoxidase (MPO), TNF‐α, interleukin‐6 (IL‐6), and interleukin‐1β (IL‐1β), down‐regulating TLR4, phosphorylated‐NF‐κB (p‐NF‐κB), phosphorylated‐IκBα (p‐IκBα), and COX2 expression in colonic tissues, and decreasing NOD‐like receptor protein 3 (NLRP3), Caspase‐1, and IL‐1β protein expression in lipopolysaccharide (LPS)‐stimulated RAW264.7 cells. These results indicate that CIN alleviates DSS‐induced colitis inflammation by modulating TLR4/NF‐κB signaling pathway and NLRP3 inflammasome activation. Abstract :